2021
DOI: 10.3389/fpls.2021.629361
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and Transcriptome Integration Reveals Insights Into Flavor Formation of ‘Crimson’ Watermelon Flesh During Fruit Development

Abstract: Metabolites have been reported as the main factor that influences the fruit flavor of watermelon. But the comprehensive study on the dynamics of metabolites during the development of watermelon fruit is not up-to-date. In this study, metabolome and transcriptome datasets of ‘Crimson’ watermelon fruit at four key developmental stages were generated. A total of 517 metabolites were detected by ultrahigh-performance liquid chromatography–electrospray ionization–tandem mass spectrometry and gas chromatography–soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…Integrating metabolome and transcriptome is an effective tool to study metabolic mechanisms ( 47 ). Based on similar trends in the contents of indicator DAAs (input as the trait file) and the transcriptional metabolism levels of DEGs, a WGCNA was performed to explore the mechanism by which drought regulated amino acid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating metabolome and transcriptome is an effective tool to study metabolic mechanisms ( 47 ). Based on similar trends in the contents of indicator DAAs (input as the trait file) and the transcriptional metabolism levels of DEGs, a WGCNA was performed to explore the mechanism by which drought regulated amino acid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory evaluation revealed that flavor is a vital fruit quality attribute relating to the refreshing perception of watermelon, an attribute linked with VOCs ( Ramirez et al, 2020 ; Mandha et al, 2021 ). Comparative transcriptome analysis revealed ADHs genes: Cla97C01G013600, Cla97C05G089700, Cla97C01G001290 Cla97C05G095170 , and Cla97C06G118330 enhanced flavor and aroma formation of ripened watermelon fruit ( Gong et al, 2021 ). The reported genes condition the biosynthesis of VOCs 2,6-nonadienal, ( E,Z ); 2-non-enal, ( E )-; 3,6-nonadien-1-ol, ( E,Z )-; and 3-nonen-1-ol, ( Z )-, respectively ( Gong et al, 2021 ).…”
Section: Genetic Analysis Of Fruit Quality In Sweet Watermelonmentioning
confidence: 99%
“…Comparative transcriptome analysis revealed ADHs genes: Cla97C01G013600, Cla97C05G089700, Cla97C01G001290 Cla97C05G095170 , and Cla97C06G118330 enhanced flavor and aroma formation of ripened watermelon fruit ( Gong et al, 2021 ). The reported genes condition the biosynthesis of VOCs 2,6-nonadienal, ( E,Z ); 2-non-enal, ( E )-; 3,6-nonadien-1-ol, ( E,Z )-; and 3-nonen-1-ol, ( Z )-, respectively ( Gong et al, 2021 ). Previous findings pinpointed that VOCs are main flavor-forming compounds in watermelon ( Liu et al, 2012 ; Dima et al, 2014 ).…”
Section: Genetic Analysis Of Fruit Quality In Sweet Watermelonmentioning
confidence: 99%
See 1 more Smart Citation
“…The oven temperature was programmed from 40 • C (3.5 min), increasing at 10 • C/min to 100 • C, at 7 • C/min to 180 • C, at 25 • C/min to 280 • C, and hold for 5 min. Other GC-MS analytical conditions used were as described by Gong et al [39]. Volatile compounds were identified by comparing the mass spectra with the data system library (MWGC or NIST) and retention index.…”
Section: Volatile Sampling and Gas Chromatography-mass Spectrometry (...mentioning
confidence: 99%